6-Gingerol Regulates Hepatic Cholesterol Metabolism by Up-regulation of LDLR and Cholesterol Efflux-Related Genes in HepG2 Cells - Li, Xiao; Guo, Jingting; Liang, Ning; Jiang, Xinwei; Song, Yuan; Ou, Shiyi; Hu, Yunfeng; Jiao, Rui; Bai, Weibin (Frontiers in Pharmacology, 2018)
Gingerols, the pungent ingredients in ginger, are reported to possess a cholesterol-lowering activity. However, the underlying mechanism remains unclear. The present study was to investigate how 6-gingerol (6-GN), the most abundant gingerol in fresh ginger, regulates hepatic cholesterol metabolism. HepG2 cells were incubated with various concentrations of 6-GN ranging from 50-200 μM for 24 h. Results showed both cellular total cholesterol and free cholesterol decreased in a dose-dependent manner. Besides, 6-GN ranging from 100-200 μM increased the LDLR protein and uptake of fluorescent-labeled LDL. Moreover, the mRNA and protein expressions of cholesterol metabolism related-genes were also examined. It was found that 6-GN regulated cholesterol metabolism via up-regulation of LDLR through activation of SREBP2 as well as up-regulation of cholesterol efflux-related genes LXRα and ABCA1.